Probiotic biofilm modified bioceramics for bone defect healing via osteogenesis, angiogenesis, and immune modulation - Su, Junwei; Gu, Huiyun; Huang, Xiang; Yuan, Ying; Zhao, Yunchang; Yang, Fan; Zhao, Yong (Frontiers in Pharmacology, 2025)
The failure to repair bone defects in a timely manner has a detrimental effect on patients’ quality of life and functional status. Consequently, there are increasing demands for medical interventions to promote healing of bone defects. However, the local inflammation induced by implants and the side effects associated with the systemic use of drugs have prompted research into the development of bioactive materials. Recent reports have indicated that oral administration of Lactobacillus acidophilus (LA) can act as an immunomodulator. In this study, we have strategically designed bioceramic scaffolds modified with inactivated LA biofilms (LA@BC) through UV irradiation for localized application of LA. The biosafety of the scaffold was validated at the cellular and animal levels to ensure that it can be safely used without bacteraemia. LA@BC achieved M1 to M2 polarization of macrophages in vitro by reducing the secretion of inflammatory factors. In addition, LA@BC enhanced the osteogenic effect of bone marrow mesenchymal stem cells by modulating the Wnt/β-catenin signaling pathway. Furthermore, osteogenesis and angiogenesis complement each other. LA@BC exerted a positive effect on the angiogenic effect of endothelial cells. In a rat cranial defect model, LA@BC upregulated the expression of RUNX2, OCN, CD31, and IL-10 in tissues, again demonstrating potent immunomodulatory and osteogenic effects. In conclusion, this bioactive scaffold provides a new strategy for clinical bone repair.